2010
DOI: 10.1248/cpb.58.843
|View full text |Cite
|
Sign up to set email alerts
|

Three New Oligostilbenes from the Seeds of Paeonia suffruticosa

Abstract: NotePaeonia suffruticosa ANDR. (Paeoniaceae) is found extensively in China. It is an important Chinese medicinal plant from the section Moutan of the genus Paeonia. This genus consists of ca. 35 species placed in three sections: Moutan, Oneapia, and Paeonia.1) The root cortex of this plant (Chinese name: mudanpi) is a well-known Chinese herbal medicine widely used as an analgesic, anaphylactic, antioxidative, and antiinflammatory agent. Numerous studies on the chemistry and pharmacology of this species have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 14 publications
2
40
0
Order By: Relevance
“…Thirdly, the steric arrangement and conformation of oligostilbenes also affected their antitumor activity. cis-and trans-suffruticosol D and cis-and trans-gnetin H are both trimers of resveratrol and both possess seven hydroxyl groups, differing only in their three-dimensional structures (16). Generally cis-and trans-gnetin H was 2-10 times more potent than cis-and trans-suffruticosol D, indicating that three-dimensional structures have a significant effect on cytotoxicity.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Thirdly, the steric arrangement and conformation of oligostilbenes also affected their antitumor activity. cis-and trans-suffruticosol D and cis-and trans-gnetin H are both trimers of resveratrol and both possess seven hydroxyl groups, differing only in their three-dimensional structures (16). Generally cis-and trans-gnetin H was 2-10 times more potent than cis-and trans-suffruticosol D, indicating that three-dimensional structures have a significant effect on cytotoxicity.…”
Section: Discussionmentioning
confidence: 96%
“…In 2003, Kang et al (7) isolated viniferin, trans-gnetin H and suffruticosol B from P. lactiflora and evaluated their effects on the proliferation and apoptosis of HL-60 cells. In our previous studies, we conducted several phytochemical analyses of the seedcases of P. suffruticosa and found that oligostilbenes were the major active ingredients, accounting for ~20% of the content (up to 200 mg/g) (9,10,16,17). In addition to their high abundance, some oligostilbenes identified in the seeds of Paeonia, such as suffruticosol A-C, have never been reported in other plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This genus comprises ~35 species that are classified into three groups: Oneapia, Paeonia, and Moutan (5). The Cortex Moutan (root cortex) of Paeonia has been recorded by China's Pharmacopoeia as a significant source of herbal medicine (6).…”
Section: Introductionmentioning
confidence: 99%
“…The Cortex Moutan (root cortex) of Paeonia has been recorded by China's Pharmacopoeia as a significant source of herbal medicine (6). Extracts of Paeonia have been shown to possess cytotoxic, antitumor, anti-inflammatory and anti-oxidative activities (5). Previous photochemical research on Paeonia identified >260 bioactive compounds, including phenols, monoterpenoidglucosides, paeonols, flavonoids, tannins, steroids, triterpenoids and stilbenes (7).…”
Section: Introductionmentioning
confidence: 99%